Principal Supervision in Improving the Quality of Learning Administration Services at the State Islamic Elementary School - Mariani, Ari; Warlizasusi, Jumira; Usman, Muhammad Umair Khan; Harahap, Emmi Kholilah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The improvement of learning administration services at the Madrasah is strongly influenced by managerial supervision from the madrasah head and the head of the administration, which includes planning, organizing, implementing, and evaluating. This study aims to describe the role of managerial supervision in improving learning administration services at Madrasah Ibtidaiyah Negeri (MIN) 03 Kepahiang. This research focuses on how the school principal and head of administration implement supervision to enhance the quality of administration, including program planning, organizing, implementation, and evaluation. The research method used is descriptive qualitative, with research subjects including the principal, deputy principal for curriculum, head of administration, and several teachers. Data were collected through observations, interviews, and documentation. Data analysis was performed using data reduction, data presentation, and conclusion. The findings of the study indicate that the managerial supervision carried out by the principal and head of administration at MIN 03 Kepahiang has successfully improved the quality of learning administration services. The structured supervision program helped assess and develop the performance of learning administration services. The school principal carried out supervision effectively, contributing to an overall improvement in the quality of education. This study recommends that the school principal continue to enhance ongoing supervision and provide training for administrative staff to strengthen the planning and organizing of learning programs more effectively.